2022
DOI: 10.1038/s41593-022-01024-6
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala and anterior cingulate transcriptomes from individuals with bipolar disorder reveal downregulated neuroimmune and synaptic pathways

Abstract: Recent genetic studies have identified variants associated with bipolar disorder (BD), but it remains unclear how brain gene expression is altered in BD, and how genetic risk for BD may contribute to these alterations. Here, we obtained transcriptomes from subgenual anterior cingulate cortex and amygdala samples from post-mortem brains of individuals with BD and neurotypical controls, including 511 total samples from 295 unique donors. We examined differential gene expression between cases and controls, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 82 publications
3
36
0
Order By: Relevance
“…Similarly, several studies have demonstrated that aspirin attenuates NF-κB elicitation [ 99 , 112 ]. These findings corroborate the accumulating data attesting to altered NF-κB activity/levels in bipolar patients [ 18 , 89 , 113 , 114 ]. In preliminary rat experiments in our lab [Uzzan, Shvartsur and Azab–personal communication] exploring whether chronic low-dose Li or low-dose aspirin, as compared with their combination, influence NF-κB activity, FC, HT and HC nuclear p65 levels were measured.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, several studies have demonstrated that aspirin attenuates NF-κB elicitation [ 99 , 112 ]. These findings corroborate the accumulating data attesting to altered NF-κB activity/levels in bipolar patients [ 18 , 89 , 113 , 114 ]. In preliminary rat experiments in our lab [Uzzan, Shvartsur and Azab–personal communication] exploring whether chronic low-dose Li or low-dose aspirin, as compared with their combination, influence NF-κB activity, FC, HT and HC nuclear p65 levels were measured.…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned, a large body of data suggested that inflammation contributes to the pathophysiology of mental disorders (15,22,(125)(126)(127)(128)(129)(130)(131)(132). For example, several research papers reported increased IL-6 levels in patients with major depression (129, 130, 133), bipolar disorder (129, 131) and schizophrenia (129, 130).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 22, 2022. ; https://doi.org/10.1101/2022.09.21.508852 doi: bioRxiv preprint Synapse dysfunction has long been considered as a mechanism underlying SCZ and BP pathophysiology, and is implicated by human genetics and gene expression studies (Jaffe et al, 2018;Mullins et al, 2021;Singh et al, 2022;Trubetskoy et al, 2022;Zandi et al, 2022). We observed reductions in a variety of canonical PSD proteins in SCZ and BP synapses, including glutamate receptors (AMPA, NMDA, and Kainate receptors), glutamatergic signaling pathway molecules (e.g., PLCB1, APP), and postsynaptic scaffolding proteins (e.g., HOMER1 and SHANK3), which supports the large body of evidence implicating glutamatergic receptor signaling impairment as a key pathomechanism in SCZ and BP.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 22, 2022. ; https://doi.org/10.1101/2022.09.21.508852 doi: bioRxiv preprint associated with synaptic function (Mullins et al, 2021). Transcriptomic analyses from postmortem brains have also implicated synaptic pathways in pathophysiology of SCZ and BP (Jaffe et al, 2018;Zandi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation